Description and interpretation of a Megatherium Americanum atlas with evidence of human intervention - Chichkoyan, Karina V. (2017)
Fil: Chichkoyan, Karina V. Universitat Rovira i Virgili. Institut Català de Paleoecologia Humana i Evolució Social; España